Hubungan Penerapan Sistem Informasi Akuntansi Manajemen dengan Prestasi Manajer Pusat Laba - Edward K. Sinuraya (Jurnal Akuntansi)
This study was carried out the PT. NINDYA KARMA (Persero), one big constructional which has been qualified as one of the group "A" contractors that are officially registered in the list of prospective working partners of the government in Bandung. It has been selected because of its rank with its "A" qualification, which can be considered to have the capacity to delegate its managers to deal with planning, operating, and controlling projects. The purpose of this study is to find out the extent of the relationship between the management information system and the performance in each division of the company. The hypothesis in this study is that the management accounting information system are positively correlated with profit center manager performance. The variables tested are the internal accounting as dependent variables (X) and independent variable (Y) as the profit center management. The result showed that Spearman rank correlation was 0,983 while the tolerable deviation in the table with a' = 0.05 showed rs = 0.73972. This means that Ho is rejected since the calculated rs is greater that its value in the rs is greater that its value in the rs table with a = 0.05. as result it can be said that management accounting information system and the performance of the profit manager are strongly related.